PENERAPAN HUKUMAN PIDANA MATI PERSPEKTIF HUKUM ISLAM DI INDONESIA - Rizal, Muhamad (Nurani, 2015)
Abstract: The existence of death penalty is still believed to be adeterrent effect to the perpetrators Overview of Islamic lawagainst the practice of the death penalty in Indonesia is alongthe death sentence is in line with the five objectives of Islamiclaw which is to establish and maintain religious, soul, mind,honor and lineage, especially highly relevant references verdictbased on the Al - Quran and al - Hadith in setting jarimah or acrime and punishment, the death penalty in Indonesia relevantto Islamic law, the mechanisms are not necessarily the same inthe context of the textual and practical in Islam..ملخص: لا یزال یعتقد وجود عقوبة الإعدام أن یكون الأثر الرادع ل مرتكبي لمحة عامة عنالشریعة الإسلامیة ضد ممارسة عقوبة الإعدام في إندونیسیا على طول حكم الإعدام تماشیا معالأھداف الخمسة للشریعة الإسلامیة التي ھي لإنشاء وصیانة الدیني، والروح، والعقل،والشرف و النسب، الحكم المراجع وخاصة ذات الصلة للغایة على أساس آل القرآن و آلالحدیث في وضع العقوبات أو جریمة جنائیة، و عقوبة، وعقوبة الإعدام في إندونیسیا ذاتالصلة للشریعة الإسلامیة، و الآلیات لیست بالضرورة ھي نفسھا في سیاق النصوص وعمليفي الإسلام.Kata Kunci: hukuman mati, hukum islam